Atmosphere Clouds Model Algorithm for Solving Optimal Reactive Power Dispatch Problem - Lenin Kanagasabai; B.Ravindranath Reddy; M.Surya Kalavathi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2014)
In this paper, a new method, called Atmosphere Clouds Model (ACM) algorithm, used for solving optimal reactive power dispatch problem. ACM stochastic optimization algorithm stimulated from the behavior of cloud in the natural earth. ACM replicate the generation behavior, shift behavior and extend behavior of cloud. The projected (ACM) algorithm has been tested on standard IEEE 30 bus test system and simulation results shows clearly about the superior performance of the proposed algorithm in plummeting the real power loss.